The Political Economy of Working-Class Social Media Commerce: Digital Capitalism and the Engelsian Concept of Working-Class “Property” - Suddhabrata Deb Roy (tripleC: Communication, Capitalism & Critique)
Social Media platforms, from being simply a mode of communication, have, recently, evolved into digital “marketplaces”, which have been facilitating the exchange of commodities within the working-class. In addition to the digitalisation of the medium of exchange value creation, which gives the worker a certain amount of regulated autonomy, this has also reinvigorated the debate about owning property and its utilisation for credit and profit generation by the working-class. The term ‘Property’ in the paper is not restricted to real estate property but encompasses everything which has the potential to generate an exchange value for its owner. The paper generalises Engels’s ideas about property owned by the workers from two of his major works, “The Housing Question” and “The Condition of the Working-Class in England” and uses the same to analyse the political economy and growing popularity of social media-based commerce among the working-class. Through data collected from the university town of Dunedin in Aotearoa, New Zealand, a town with an extensive and established system of social media-based commerce, the paper puts forward the relevance of the Engelsian critique of the idea of uplifting the working-class simply by giving them control over the possession of property, in the age of digital capitalism. In doing so, the present paper talks about how digital capitalism utilises social media and its associated platforms for commercial exchange to keep the cycle of accumulation in the capitalist social system intact by further exploiting the working-class.